Second-Order Raman Scattering in Exfoliated Black Phosphorus - Favron, Alexandre; Goudreault, Félix Antoine; Gosselin, Vincent; Groulx, Julien; Côté, Michel; Leonelli, Richard; Jean-Francis, Germain; Anne-Laurence Phaneuf-L'Heureux; Francoeur, Sébastien; Martel, Richard (arXiv.org, 2024)
Second-order Raman scattering has been extensively studied in carbon-based nanomaterials, e.g. nanotube and graphene, because it activates normally forbidden Raman modes that are sensitive to crystal disorder, such as defects, dopants, strain, etc. The sp\(^2\)-hybridized carbon systems are, however, the exception among most nanomaterials, where first-order Raman processes usually dominate. Here we report the identification of four second-order Raman modes, named \(D_1\), \(D_1'\), \(D_2\) and \(D_2'\), in exfoliated black phosphorus (P(black)), an elemental direct-gap semiconductor exhibiting strong mechanical and electronic anisotropies. Located in close proximity to the \(A^1_g\) and \(A^2_g\) modes, these new modes dominate at an excitation wavelength of 633 nm. Their evolutions as a function of sample thickness, excitation wavelength, and defect density indicate that they are defect-activated and involve high-momentum phonons in a doubly-resonant Raman process. Ab initio simulations of a monolayer reveal that the \(D'\) and \(D\) modes occur through intravalley scatterings with split contributions in the armchair and zigzag directions, respectively. The high sensitivity of these \(D\) modes to disorder helps explaining several discrepancies found in the literature.